Effects of temperature, humidity, air quality and anthropic activities on the transmission of SARS-CoV-2: a systematic review protocol. Issue 11 (4th November 2020) - Jeevananthan, Chandrika; Muhamad, Nor Asiah; Jaafar, Mohd Hasni; Hod, Rozita; Ab Ghani, Rimah Melati; Md Isa, Zaleha
Abstract : Introduction: The current global pandemic of the virus that emerged from Hubei province in China has caused coronavirus disease in 2019 (COVID-19), which has affected a total number of 900 036 people globally, involving 206 countries and resulted in a cumulative of 45 693 deaths worldwide as of 3 April 2020. The mode of transmission is identified through airdrops from patients' body fluids such as during sneezing, coughing and talking. However, the relative importance of environmental effects in the transmission of the virus has not been vastly studied. In addition, the role of temperature and humidity in air-borne transmission of infection is presently still unclear. This study aims to identify the effect of temperature, humidity and air quality in the transmission of SARS-CoV-2. Methods and analysis: We will systematically conduct a comprehensive literature search using various databases including PubMed, EMBASE, Scopus, CENTRAL and Google Scholar to identify potential studies. The search will be performed for any eligible articles from the earliest published articles up to latest available studies in 2020. We will include all the observational studies such as cohort case–control and cross-sectional studies that explains or measures the effects of temperature and/or humidity and/or air quality and/or anthropic activities that is associated with SARS-CoV-2. Study selection and reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Meta-Analysis of Observational Studies in Epidemiology guideline. All data will be extracted using a standardised data extraction form and quality of the studies will be assessed using the Newcastle-Ottawa Scale guideline. Descriptive and meta-analysis will be performed using a random effect model in Review Manager File. Ethics and dissemination: No primary data will be collected, and thus no formal ethical approval is required. The results will be disseminated through a peer-reviewed publication and conference presentation. PROSPERO registration number: CRD42020176756.